Eskers and Heavy Mineral Prospecting, Northeastern Minnesota - Brown, Timothy Reed (1988)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Timothy Reed Brown in partial fulfillment of the requirements for the degree of Master of Science, January 1988. There is 1 supplementary file also attached to this record, which contains Plate 1 referenced in the thesis. Mineral exploration in heavily glaciated terrain is difficult because a mantle of glacial drift generally covers the bedrock. Eskers and the heavy minerals they contain were studied to (1) determine their potential use as a prospecting tool, and (2) better understand the dynamics of esker formation. Studies emphasized paleohydraulics, origin of esker sediment, lithology, and mineralogy. 'IWo main types of eskers are recognized in northeastern Minnesota on the basis of their morphology, sedimentology, and origin. Continuous eskers form as a single, continuous segment when an ice sheet is stagnant, or nearly stagnant. Meltwater flowing through an ice tunnel deposits sediment in both the tunnel and onto an adjacent outwash plain. Melting of the tunnel walls induces inflow of the ambient ice which leads to the influx of rock debris. Seasonal fluctuations of meltwater discharge leave a sedimentary sequence characterized by a wide variety of grain sizes (medium-grained sand to boulders) and bedforms (climbing ripples, massive beds, and planar, trough, and graded cross beds). Be2ded eskers are a series of consecutive segments, or beads, that are separated by swamps or lakes, and whose trends follow the low ground between the drumlins of the Toimi Drumlin Field. A limited range of bedforms (massive beds and trough cross beds) and grain sizes (mostly bouuders) are exposed in the beaded eskers. Other sedimentary features may be present, but they are covered by the surrounding swamp deposits and not exposed. Individual segments of the beaded esker system probably form at the margin of an actively retreating ice sheet as an annual deposition event. Average distances between successive bead crests imply an annual ...